The Impact of Population Growth on the Services Sector in the City of Mafraq - Ayed Taran (My University, 2016)
The aim of this study was to investigate the impact of population growth on the services sector (education and health), the study relied on two approaches descriptive and analytical which are based on the study of population growth of the city and development in the field of services at different stages of the processing of data and information gathered from various sources to achieve the objectives of the study. The study found a number of results, including: that the rate of population growth in the city of Mafraq during the period (1952-2004) was higher than the rate of evolution in the fields of different services, due to the large increase in the number of population due to natural increase and migration from other regions, as The study found that educational services suffer from overcrowding in the number of private students in the basic stages in addition to the poor in their distribution, and health services are suffering from great overcrowding in the number of patients reviewers primary health centers in the city, posing great pressure them and reflected in the level of health services provided to citizens. The study recommends a review of the previous master plans for the city taking into account the reality of modern regulatory developments and population growth that has occurred over the city, and the provision of public services and facilities to cope with the growing numbers to suit the city's community groups in all fields’ requirements.

تهدف هذه الدراسة التعرف إلى مدى اثر النمو السكاني على قطاع الخدمات (التعليمية والصحية)، واعتمدت الدراسة على المنهجين الوصفي والتحليلي اللذان يقومان على أساس دراسة النمو السكاني للمدينة والتطور في مجال الخدمات في مراحل مختلفة لمعالجة البيانات والمعلومات التي تم جمعها من مصادرها المختلفة لبلوغ أهداف الدراسة. وتوصلت الدراسة إلى عدد من النتائج أهمها: أن معدل النمو السكاني في مدينة المفرق خلال الفترة (1952-2004) كان أعلى من معدل التطور في مجالات الخدمات المختلفة، ويعزى ذلك إلى الزيادة الكبيرة في أعداد السكان الناجمة عن الزيادة الطبيعية والهجرة من المناطق الأخرى، كما توصلت الدراسة إلى أن الخدمات التعليمية تعاني من اكتظاظ في أعداد الطلاب خاصة في المراحل الأساسية بالإضافة إلى سوء في توزيعها، كما أن الخدمات الصحية تعاني من اكتظاظ كبير في أعداد المرضى المراجعين للمراكز الصحية الأولية في المدينة مما شكل ضغطا كبيرا عليها وانعكس ذلك على مستوى الخدمات الصحية التي تقدمها للمواطنين. وتوصي الدراسة بإعادة النظر في المخططات الهيكلية السابقة للمدينة مع مراعاة الواقع والمستجدات التنظيمية الحديثة والنمو السكاني الذي طرا على المدينة، وتوفير الخدمات والمرافق العامة لمواجهة الأعداد المتزايدة بحيث تتناسب مع متطلبات فئات مجتمع المدينة في كافة المجالات.
أثر النمو السكاني على قطاع الخدمات في مدينة المفرق